Synthesis, Biological Evaluation and Docking Studies of Functionalized Pyrrolo[3, 4‐b]pyridine Derivatives. Issue 9 (2nd March 2021) - Saigal,; Ghanem, Younes S. A.; Uddin, Amad; Khan, Sarfaraz; Abid, Mohammad; Khan, Md. Musawwer
Abstract: The synthesis and antibacterial studies of polysubstituted pyrrolo[3, 4‐ b ]pyridine derivatives have been described. The preparation of pyrrolo[3, 4‐ b ]pyridine derivatives was carried out by the reaction of enamino imides, aromatic aldehydes and malononitrile/ethyl cyanoacetate using 10 mol % of DBU (1, 8‐diazabicyclo[5.4.0]undec‐7‐ene) in ethanol at 78 °C in good yields. The compounds were characterized by standard spectroscopic techniques including IR, 1 H & 13 C NMR and elemental analysis and also final confirmation was done by single crystal X‐ray. The antibacterial activity of all the synthesized compounds was tested against two Gram positive ( S. pneumoniae MTCC 655 and E. faecalis MTCC 439) and three Gram negative ( E. coli ATCC 25922, S. typhimurium MTCC 3224, and P. aeruginosa MTCC 2453) bacterial strains. Most of the tested compounds showed moderate to good antibacterial activity. Compounds pyrrolo[3, 4‐ b ]pyridine derivatives (4 j and 4 l ) were the most potent and displayed bactericidal activities against E. coli strain with MIC (minimum inhibitory concentration) values of 62.5 μg/mL and 125.0 μg/mL respectively. Growth kinetic studies against E. coli, toxicity studies using human RBCs (red blood cells) and also docking studies of the selected compounds 4 j and 4 l supported that these compounds inhibit the growth of bacterial cells, non‐toxic in nature and interact with key amino residues of DNA (deoxyribonucleic acid) duplex (PDBID: 1BNA) and have drug‐like properties. Abstract : Herein, we developed a three‐component reaction of enamino imides, aryl aldehydes and malononitrile for the synthesis of functionalized pyrrolo[3, 4‐ b ]pyridines as an antibacterial agent. In silico ADMET predictions and docking studies were carried out to investigate the mode of interaction of the lead molecules with DNA and also their drug‐like properties.